Philological Studies and Discussion of Human Obligations in the Manuscript of Raos Jawi Panêmbah Gangsal Prakawis - Widya Ayu , Setiani; Ekowati, Venny Indria; Mulyani, Hesti; Prastowo, Galang (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
The Raos Jawi Panêmbah Gangsal Prakawis manuscript is an ancient manuscript that contains human obligations worldwide. This text is interesting to research because it presents the concept of obligation from the perspective of Islamic teachings, which is integrated with the cultural values ​​of Javanese society. This research, which examines ancient Javanese manuscripts, aims to present the Raos Jawi Panêmbah Gangsal Prakawis manuscript through philological studies and explain the contents of the text regarding human obligations. This research uses modern philological and descriptive research methods. Research data was collected through philological research steps: manuscript inventory, manuscript description, text transliteration, text editing, text paraphrasing, and text translation. Data were analyzed using descriptive analysis techniques. The research results showed that (1) one copy of the manuscript was found; (2) the condition of the manuscript is good and the text can be read clearly; (3) transliteration results in the transfer of Javanese script to Latin; (4) there are four errors in writing the text; (5) paraphrasing produces text in the form of gancaran; (6) there are three categories of human obligations, namely absolute obligations towards God and the Messenger, general obligations towards kings, and positive obligations towards teachers and parents.